TRANSFORMASI KUDUS SEBAGAI KOTA LAYAK ANAK ( Tinjauan atas Pemenuhan Hak Sipil dan Partisipasi ) - Siti Malaiha Dewi (Muwazah, 2011)
Abstract: Children are a gift of God's mandate and at the same time that always must be maintained. Unfortunately, some cases such as child exploitation, child sexual abuse, trafficking, was just always there. In fact, the City of Eligible Children (KLA) has long been proclaimed. Kudus, is one of them. The research is to know "Why is the implementation of the KLA in particular compliance with civil rights and child participation has not materialized". The results of civil rights compliance situations and children's participation is still minimal. This can be seen from the following indicators: 1) There are still 30% of children who do not have birth certificates of children; 2) involvement of children in public policy decisions not yet exist; 3) Lack of information and communication center-based child; Only the fourth indicator of presence forum child in the Kudus District are met. Obstacles in the implementation KLA in Kudus City were: 1) Program of the KLA is considered as a program that is not sexy and not able to boost the image of officials, 2) Institutionally, egosektoral SKPD is still so difficult to integrate the issue of children into the program all SKPD , 3) Institutional Capacity inadequate implementation, and 4) specific budget for children not in the budget.